THE EFFECT OF SYSTEM QUALITY, INFORMATION QUALITY, AND SERVICE QUALITY ON CUSTOMER SATISFACTION IN ORDERING FOOD THROUGH JUANGJEK APPLICATION (Study On JuangJek Application Users In Bireuen Regency) - Haidar Khawarizmi; Muchsin; Heriyana; Samsul Bahri (RADJA PUBLIKA, 2024)
This study aims to determine how the influence of system quality, information quality, and service quality on customer satisfaction in ordering food through the JuangJek Application in Bireuen Regency. The quality indicators of the system used consist of ease of use, accessibility, interactivity, and website innovativeness. Then information quality indicators consist of intrinsic information quality, contextual information quality, representation information quality, and accessibility information quality. Furthermore, service quality indicators consist of tangibles, reliability, responsiveness, assurance, and emphaty. While customer satisfaction indicators consist of overall satisfaction, confirmation of expectations, delivery speed, application satisfaction, and repurchase intention. The data used in this study was primary data obtained by distributing questionnaires to 110 JuangJek Application users in Bireuen Regency. The data analysis technique used in this study is multiple linear regression analysis using the help of SPSS software version 26. The results showed that system quality, information quality, and service quality had a positive and significant effect on customer satisfaction in ordering food through the JuangJek Application in Bireuen Regency.